2016
DOI: 10.15388/klbt.2014.7676
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in discussion sessions of conference presentations: theoretical foundations for a multimodal analysis

Abstract: Discussions sessions have not received much attention within the genre of conference presentations. In this paper, we present the theoretical framework that underlies the approach followed to analyse the multimodal expression of evaluation. Then, an example of the application of the study has been considered necessary to understand it. Corpus linguistics provided the indications to collect the corpus, annotate it and find the appropriate software to digitalise the relevant information for the study. Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…These gestures are in pragmatic synchrony with the speech and the intonation showing, as the semantic meaning of 'no les tengo que decir' (there's no need to tell you) shows, intensification of the confirmation of his words and tries to include the audience (a ustedes / nosotros) (to you / us) using what is called pluralisations markers (McClave 2000) (lateral movements with inclusive pronouns). These results are in line with previous studies (Querol-Julián, 2011;Fortanet and Querol-Julián 2012), which show how head nods intensify the semantic interpretation of the discourse.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These gestures are in pragmatic synchrony with the speech and the intonation showing, as the semantic meaning of 'no les tengo que decir' (there's no need to tell you) shows, intensification of the confirmation of his words and tries to include the audience (a ustedes / nosotros) (to you / us) using what is called pluralisations markers (McClave 2000) (lateral movements with inclusive pronouns). These results are in line with previous studies (Querol-Julián, 2011;Fortanet and Querol-Julián 2012), which show how head nods intensify the semantic interpretation of the discourse.…”
Section: Resultssupporting
confidence: 93%
“…However, only a few highlight the importance of Multimodal Discourse Analysis (MDA) and even fewer analyse spoken academic discourse. MDA argues that all discourse is inherently multimodal and it is not possible to achieve a comprehensive understanding of spoken discourse unless both linguistic and non-linguistic features are jointly analysed (Baldry & Thibault, 2006;O'Halloran, 2004;Querol-Julián, 2011;Querol-Julián and Fortanet, 2012). The study of multimodality in language and language systems often focuses its attention on interaction, which is examined from two perspectives: human-to-human interaction (Norris, 2004) and human-machine interaction (Roope, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study exhibited in this article has followed a methodological framework for analysis applied in previous Multimodal Discourse Analysis studies on spoken academic discourse (Querol-Julián, M 2011;QuerolJulián, M. & I. Fortanet-Gómez, 2013;Fortanet-Gómez, I. & M. N. RuizMadrid, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Gaze and especially gaze directions (Goodwin, 1981(Goodwin, , 1994 were typically combined with head movements. Gaze might not be always continuous in an interaction (Querol-Julián, 2011), and indeed, data revealed that participants changed gaze directions over the course of the conversation. The data also showed examples in which both participants looked at each other when interacting as well as situation in which the 'hearer', in this case the complainee, tended to look more at the complainer than the complainer looked at the complainee (Goodwin, 1981), possibly due to the difficulty to performing a FTA.…”
Section: Overall Communicative Eventmentioning
confidence: 99%